Efeito neuroprotetor do ácido clorogênico e cafeína em um modelo animal da doença de Alzheimer esporádica induzida por estreptozotocina - Bezerra, Jéssica Rabelo (2023)
Alzheimer's Disease (AD) is a progressive neurodegenerative disease characterized by the formation of amyloid plaques and intracellular neurofibrillary tangles in cortical areas, leading to progressive memory loss and cognitive impairments, and it is the most common form of dementia. Intracerebroventricular injections of streptozotocin (ICV-STZ) have been used as an experimental model of sporadic AD (SAD) in rodents due to their ability to impair brain insulin signaling, induce oxidative stress, neuroinflammation, and dysfunctions in neurogenesis, as well as cognitive decline, which are characteristic features of SAD. Chlorogenic Acid (CGA) and Caffeine (CAF), the main compounds found in coffee, have properties such as glucose metabolism modulation, antioxidant and anti-inflammatory effects, which have already been described. The objective of this study was to investigate the effects of CGA and CAF on cognitive deficits, neuronal damage, and neuroinflammation in mice subjected to the experimental model of ICV-STZ-induced SAD. Male Swiss mice (25-35 g) received bilateral ICV-STZ (3 mg/kg, 1.5 µl) on days 1 and 3 of the experiment. Treatment with CGA (5 mg/kg, orally) and CAF (15 mg/kg, orally) or vehicle (water, orally) was administered for 26 days, starting 2 hours after the second induction procedure. Blood glucose levels of the animals were measured before and after the induction of SAD. The results demonstrated that there were no significant alterations in blood glucose levels. ICV-STZ caused deficits in aversive, recognition, and spatial memory. Treatment with CGA and CAF protected against deficits in aversive, recognition, and spatial memory. Locomotor activity, working memory, and anxiety-related parameters were not altered. ICV-STZ resulted in increased concentrations of nitrite/nitrate and MDA. Treatment with CGA and CAF protected against the increase in nitrite/nitrate and MDA concentrations in the cortex and hippocampus. Treatment with CGA and CAF protected against increased concentrations of nitrite/nitrate and MDA in the cortex and hippocampus. ICV-STZ caused a decrease in viable neurons, BDNF depletion and astrogliosis and microgliosis in the cortex and hippocampus. Treatment with CGA and CAF protected against decreased viable neurons and BDNF depletion and prevented astrogliosis and microgliosis in the prefrontal cortex and hippocampus. Molecular docking analyses showed that CGA and CAF strongly interact with the acetylcholinesterase (AChE) and insulin receptors (IRS-1). These results suggest that the neuroprotective activity of CGA and CAF is related to their antioxidant, anti-inflammatory, and neuronal integrity maintenance properties, highlighting their therapeutic or adjuvant potential for the treatment of SAD.